Management of patients with Major Depressive Disorder in the context of Primary Health Care: a literature review (Research, Society and Development, 2022)
Objective: to investigate, in the national and international literature, the characteristics of the behavior of patients with Major Depressive Disorder in the scope of Primary Health Care. Methods: this is an Integrative Literature Review (IRL), with a sensitive and specific search in the databases. data: Virtual Health Library (VHL), PubMed and Cochrane Library, through the terms and their correlates: “Therapeutics”, “Major Depressive Disorder”, “Primary Health Care” and “Family Doctors”. Results: We identified 518 studies, after applying the eligibility criteria 20 studies included in the qualitative synthesis, which were published in eight different countries from 1995 to 2020, changed total population of 35,590 patients with major depressive disorder. Discussion: evasion studies addressed pharmacological and non-pharmacological measures in intervention, such as psychotherapy and health education, as well as alternative measures, such as care management. Conclusion: the methods used were dissipation in the treatment of depression, but few studies on the subject were used in Brazil.